Machine learning for kids : a project-based introduction to artificial intelligence - Lane, Dale (No Starch Press, Inc., 2021)
"An introduction to machine learning and artificial intelligence, using the Scratch programming language. Provides instructions to make a game that can learn hand motions, a chatbot that can answer questions, a computer assistant that can learn simple commands, and more"--